Pengembangan media pembelajaran berbasis wordwall pada mata pelajaran ipas materi bumi berubah untuk meningkatkan hasil belajar siswa kelas V sekolah dasar - khoiriyah, soviyatul; Sumadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this study is to produce and develop a valid, practical, and effective learning media product based on Wordwall for fifth-grade students. This study is a research and development (R&D) study using the ADDIE model (Analyze, Design, Development, Implementation, and Evaluation). The subjects of the study consisted of 17 fifth-grade students, the fifth-grade teacher at UPT SDN Sukoharjo, and three validators. Data was collected through several instruments, including observation sheets, student and teacher interview sheets, expert validation sheets, student and teacher response questionnaires, and student test sheets. Data analysis was conducted using qualitative and quantitative data analysis techniques, where the collected data was examined for validity, practicality, and effectiveness. This study concluded that the Wordwall-based learning media is suitable for use based on the percentage scores obtained from media experts (80%), subject matter experts (80%), and language experts (82.2%), each of which met the validity criteria. The effectiveness data from the student test was 70%, categorized as sufficiently effective. Additionally, the practicality data from the student response questionnaire was 96% and the teacher response was 96%, meeting the criteria for highly practical. Based on the data obtained, it can be concluded that the Wordwall-based learning media meets the criteria for validity, practicality, and effectiveness as a learning medium